Classification hiérarchique des zones boisées d’altitudes de l’île d’Anjouan, Comores - Houmadi Amélaïd; Pascal Fust; Kathleen Green; Mohamed Daniel; Ishaka Said; Joelisoa Ratsirarson; Steeves Buckland (VertigO)
The second largest island of the Comoros archipelago, Anjouan, was covered by forest before human colonization, whereas today only a few forest fragments remain on steep and inaccessible slopes. Under human pressure, the loss of forests to make place for agricultural areas continues. The present study investigated the vegetation of Anjouan to determine which habitat types can be found on the island. In 2010, we collected data on vegetation composition using a plot-based methodology. Two types of analyses were used to partition the habitat into different classes : principal component analysis (PCA) and hierarchical cluster analysis (HCA). Six habitat classes were identified : plantations in high altitude open areas, plantations in less wooded areas, low altitude agroforestry, severely degraded and under-planted forest, degraded forest and dense natural forest. The first four classes were associated with agricultural activities in varying intensities. Significant differences between habitat classes were distinguished by Kruskal-Wallis tests for tree densities (native and non-native), species diversification, and level of agricultural exploitation. The findings show that the vegetation cover in Anjouan is marked by human exploitation, which requires monitoring to avoid over-exploitation of the last remaining natural forests on the island. The results of this study will be used for the agroforestry management planning and the implementation of conservation actions for forest habitats on the island.